Effects of base metal state on the microstructure and mechanical properties of Al–Mg–Si alloy friction stir-welded joints. (August 2020) - Xu, Z.Z.; Liu, C.Y.; Zhang, B.; Huang, H.F.; Cheng, W.
Highlights: The grains and insoluble phase sizes and structures of the FSW joints were not affected by BM state; The composition of precipitated phases in the FSW joints depended on the BM state; The WQ-AA FSW joint exhibited the highest hardness and YS; The WQ-NA FSW joint exhibited the highest UTS and EL. Abstract: Al–Mg–Si alloys with different heat treatment states were used as base metals (BMs) in investigating the effect of BM state on the microstructure and mechanical properties of Al–Mg–Si alloy friction stir-welded (FSW) joints. The Al grains and insoluble phases of the FSW joints were not affected by BM state, but the compositions of the precipitated phases in the heat-affected zones (HAZs) and nugget zones (NZs) depended on the phase compositions of the BMs. The FSW joint that was welded using the BM with water quenching (WQ) and artificial aging state exhibited the greatest hardness among the joints at the same zones because of the high densities of the β″ phases in the BM, the fine and high densities of the β′ phases in the HAZ, the high number of solution atoms, and the formation of Guinier–Preston zones in the NZ. Moreover, the joint exhibited the highest yield strength because of the high hardness of its HAZ, which is the fracture location in FSW joints. The FSW joint that was welded using the BM with WQ and natural aging state exhibited the highest ultimate tensile strength and tensile elongation because of its high structural uniformity.